Analysis of the IRS development from 2018 to 2024 - Wagner, Adam; Málek, Jiří, 1953-; Malinovský, Daniel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This diploma thesis examines the development of interest rate derivatives from 2018 to 2024 with a focus on interest rate swaps. The first part of the thesis is devoted to the characteristics of interest rate derivatives. In the second part, the valuation of interest rate swaps and cross-currency swaps is analysed. Scripts in Python are here created to automate the valuation of the mentioned instruments. Furthermore, possible cases of arbitrage and their causes are explored in this part. In the third and last part of the thesis, the development of the price and the use of interest rate and cross-currency swaps in practice from the perspective of the banks (especially in the Czech Republic) between the years 2018 and 2024 is analysed. This thesis aims to provide a comprehensive insight into the field of interest rate swaps and their development over the last few years.
Vedoucí práce: Jiří Málek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses